Genomic Insights Into the Distribution and Evolution of Group B Streptococcus - Chen, Swaine L. (Frontiers in Microbiology, 2019)
Streptococcus agalactiae, also known as Group B Streptococcus (GBS), is a bacteria with truly protean biology. It infects a variety of hosts, among which the most commonly studied are humans, cattle, and fish. GBS holds a singular position in the history of bacterial genomics, as it was the substrate used to describe one of the first major conceptual advances of comparative genomics, the idea of the pan-genome. In this review, I describe a brief history of GBS and the major contributions of genomics to understanding its genome plasticity and evolution as well as its molecular epidemiology, focusing on the three hosts mentioned above. I also discuss one of the major recent paradigm shifts in our understanding of GBS evolution and disease burden: foodborne GBS can cause invasive infections in humans.